Leisure sedentary time and elevated blood pressure: evidence from the statutory retirement policy - Li, Hao; Zeng, Weihong (Frontiers in Public Health, 2024)
Abstract Objectives The relationship between sedentary behaviors and elevated blood pressure remains inconclusive, and the socioeconomic mechanisms underlying the linkage are rarely discussed. Since retirement is often associated with behavioral changes that impact health, this study aims to provide evidence on changes in leisure sedentary time after the statutory retirement age on elevated blood pressure, along with the socioeconomic mechanisms. Methods We utilized data from five waves (2004–2015) of the China Health and Nutrition Survey (CHNS), focusing on males aged 55–65 employed in the formal sector. Leisure sedentary time, the independent variable, was measured based on self-reported data, while diastolic (DBP) and systolic (SBP) blood pressure were the dependent variables. Using statutory retirement policy as an exogenous variation, we employed a continuous difference-in-differences (DID) framework and a propensity score matching difference-in-differences (PSM-DID) approach to examine the relationship between changes in leisure sedentary time after the statutory retirement age and elevated blood pressure. The analysis was conducted using ordinary least squares (OLS). To address potential endogeneity, we applied the instrumental variable (IV) method via two-stage least squares (2SLS). Results Our findings indicate an increase in diastolic blood pressure after statutory retirement, attributed to increased leisure sedentary time. However, there was no significant increase in systolic blood pressure. Moreover, physical activity did not appear to offset this rise in blood pressure, while higher educational attainment and having family members employed in the medical field helped mitigate its negative effects. Conclusion This study highlights the potential adverse impact of increased leisure sedentary time on diastolic blood pressure among middle-aged men in the formal sector, while also exploring the socioeconomic factors that may alleviate these effects. These results provide a foundation for public health initiatives aimed at addressing the rising prevalence of sedentary behavior and its association with blood pressure issues.